2009
DOI: 10.1016/j.jtbi.2008.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of microparasites in spatially and genetically structured host populations: The example of RHDV infecting rabbits

Abstract: A c c e p t e d m a n u s c r i p t 2 AbstractSeveral studies have shown that classical results of microparasite evolution could not extend to the case where the host species shows an important spatial structure. Rabbit Haemorrhagic Disease Virus (RHDV), responsible for Rabbit Haemorrhagic Disease (RHD), which recently emerged in rabbits, has strains within a wide range of virulence, thus providing an interesting example of competition between strains infecting a host species with a metapopulation structure. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 60 publications
5
9
0
Order By: Relevance
“…Since G2 strains appear to be the first pathogenic strains that circulated when emergence of RHDV was observed, acquisition of A antigen recognition by subsequent strains could have allowed a better coverage of the ABH diversity and targeting of the less susceptible and positively selected A+B− animals. Collectively, the data suggest that HBGA diversity tends to restrict the virus transmission and therefore to protect the host population, which is in accordance with the results of the models developed by Fouchet et al [44].…”
Section: Discussionsupporting
confidence: 91%
“…Since G2 strains appear to be the first pathogenic strains that circulated when emergence of RHDV was observed, acquisition of A antigen recognition by subsequent strains could have allowed a better coverage of the ABH diversity and targeting of the less susceptible and positively selected A+B− animals. Collectively, the data suggest that HBGA diversity tends to restrict the virus transmission and therefore to protect the host population, which is in accordance with the results of the models developed by Fouchet et al [44].…”
Section: Discussionsupporting
confidence: 91%
“…Other non-climatic factors have also been suggested to contribute to the variable pattern of the impact of RHD in rabbit populations such as the timing of the breeding season, the presence of a related and protective RHDV-like calicivirus in rabbit populations or the negative interaction of the myxomatosis outbreaks in the populations [reviewed in [86]]. In addition, modelling studies indicated that population dynamics and spatial structure may greatly influence disease impact and host-virus co-evolution [87,88]. …”
Section: Epidemiologymentioning
confidence: 99%
“…For rabbit haemorrhagic disease virus, Fouchet et al. () showed that host genetic diversity could contribute to the persistence of strains with widely varying virulence, ultimately favouring less virulent strains.…”
Section: Questions That Spatial Models Have Been Used To Answermentioning
confidence: 99%